2015
DOI: 10.5489/cuaj.2482
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of percutaneous renal access skills during Urology Objective Structured Clinical Examinations (OSCE)

Abstract: Introduction: The first objective was to assess percutaneous renal access (PCA) skills of urology postgraduate trainees (PGTs) during the Objective Structured Clinical Examinations (OSCEs). The second objective was to determine whether previous experience with percutaneous nephrolithotomy (PCNL) improved performance. Methods: After obtaining ethics approval, we recruited PGTs from two urology programs in Quebec between postgraduate years (PGY-3 to PGY-5). Each trainee was asked to answer a short questionnaire … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
4
2
1

Relationship

2
5

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 13 publications
(22 reference statements)
0
7
0
Order By: Relevance
“…Few studies were found on assessment of PCA skills. 12,13 The biological bench models used porcine or bovine kidneys wrapped within foam, 14 foam in a mannequin, 15 silicone, 16 chicken carcass, 17,18 full-thickness skin flap, 19,20 or additional subcutaneous fascia, muscle, 21 and ribs. 22 Other nonbiological bench models used prototyping or 3D printing.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…Few studies were found on assessment of PCA skills. 12,13 The biological bench models used porcine or bovine kidneys wrapped within foam, 14 foam in a mannequin, 15 silicone, 16 chicken carcass, 17,18 full-thickness skin flap, 19,20 or additional subcutaneous fascia, muscle, 21 and ribs. 22 Other nonbiological bench models used prototyping or 3D printing.…”
Section: Resultsmentioning
confidence: 99%
“…27 The PERC MentorÔ (Simbionix, Cleveland, OH) was the only VR simulator that has been validated for training and assessment of PCA skills. 12,13,[28][29][30][31] However, none of these studies assessed the educational impact of PCA simulators in terms of transferring PCA skills from the benchtop to the OR. Furthermore, most of these studies did not address the validity and the cost of these simulators.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Such surgery is sаfe when treаting lаrge renаl stones [2]. One of the most importаnt steps of PCNL is gаining аccess to the renаl collecting system before dilаtаtion [3]. This step is frequently аssociаted with complicаtions [4].…”
Section: Introductionmentioning
confidence: 99%